2022
DOI: 10.1111/mve.12607
|View full text |Cite|
|
Sign up to set email alerts
|

D‐limonene nanoemulsion: lousicidal activity, stability, and effect on the cuticle of Columbicola columbae

Abstract: The current study was conducted to investigate the efficacy and stability of D-limonene (DL) and its nanoemulsion (DLN) against pigeon feather lice (Columbicola columbae) and their mode of action. DL pure form and DLN were prepared and characterized freshly and after storage for 50 days. In vitro bioassay on live lice was conducted with different concentrations of DL, DLN, and deltamethrin (DM). The results revealed significant mortality rates in the DL-, DLN-, DM-treated groups when compared with the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
5
0
2
Order By: Relevance
“…The increased effectiveness of nanoemulsions over pure oils is a result of the smaller droplet size of EOs, which enhances the number of active molecule interactions with the biological target membranes and promotes their transfer through them [36]. Additionally, Gadelhaq et al [37] showed that the D-limonene nanoemulsion maintains its efficacy for 2 months and has better efficacy than D-limonene in its unemulsified form. Furthermore, by lowering the LC 50 to its half value, EO nanoemulsions showed enhanced effectiveness against Aedes aegypti larvae [38].…”
Section: Discussionmentioning
confidence: 99%
“…The increased effectiveness of nanoemulsions over pure oils is a result of the smaller droplet size of EOs, which enhances the number of active molecule interactions with the biological target membranes and promotes their transfer through them [36]. Additionally, Gadelhaq et al [37] showed that the D-limonene nanoemulsion maintains its efficacy for 2 months and has better efficacy than D-limonene in its unemulsified form. Furthermore, by lowering the LC 50 to its half value, EO nanoemulsions showed enhanced effectiveness against Aedes aegypti larvae [38].…”
Section: Discussionmentioning
confidence: 99%
“…El modo de acción del Limoneno está asociado con la inhibición neuromuscular de la acetilcolinesterasa (AChE), lo que lleva a la acumulación de AChE, lo que genera excitación neuronal y la muerte del insecto (García et al, 2005;Zarrad et al, 2017;Gadelhaq et al, 2023). Además, en A. mellifera, se observaron efectos en las células intestinales, resultantes de las lesiones necróticas observadas en el epitelio.…”
Section: Discussionunclassified
“…Columbicola columbae is the main cause of ectoparasitic infections in pigeons, which can lead to symptoms such as anemia, dermatitis, decreased egg production, and slow weight gain, and the general method of counteracting this is the use of deltamethrin but this not only leads to environmental contamination but also negatively affects the pigeons and their products. Therefore, Gadelhaq et al [24] proposed the use of D-limonene instead of deltamethrin and showed that 30 mg/mL of D-limonene and its nanoemulsion exhibited equivalent lousicidal activity to 0.025 mg/mL of deltamethrin without affecting pigeons, both through the neuromuscular inhibition of AchE and contact distortion of the body wall, with the difference that D-limonene and its nanoemulsion did not affect the pigeons and, remarkably, the D-limonene nanoemulsion remained stable after 50 days of storage and exhibited significant insecticidal activity.…”
Section: Agriculturementioning
confidence: 99%
“…In recent years, research on the practical applications of D-limonene has continued; however, despite its proven bioactivity, its hydrophobicity, volatility, and sensitivity to heat, light, oxygen, and moisture are affected by environmental factors (e.g., oxygen, light, and temperature) when applied directly to food systems and its oxidation gives off unpleasant odors, which, together with its own strong aromatic odor, can interfere with the sensory properties of the food to which they are added [22], which limits its application in food [23,24]. Currently, researchers are improving the physicochemical properties and bioactivity of D-limonene by producing new materials, such as nanoemulsions and nanofilms, through encapsulation and other techniques, and applying them in practical applications [25].…”
Section: Introductionmentioning
confidence: 99%